Nitric oxide signaling modulates synaptic inhibition in the superior paraolivary nucleus (SPN) via cGMP-dependent suppression of KCC2 - Yassin, Lina; Radtke-Schuller, Susanne; Asraf, Hila; Grothe, Benedikt; Hershfinkel, Michal; Forsythe, Ian D.; Kopp-Scheinpflug, Cornelia (Frontiers in Neural Circuits, 2014)
Glycinergic inhibition plays a central role in the auditory brainstem circuitries involved in sound localization and in the encoding of temporal action potential firing patterns. Modulation of this inhibition has the potential to fine-tune information processing in these networks. Here we show that nitric oxide (NO) signalling in the auditory brainstem (where activity-dependent generation of NO is documented) modulates the strength of inhibition by changing the chloride equilibrium potential. Recent evidence demonstrates that large inhibitory postsynaptic currents (IPSCs) in neurons of the superior paraolivary nucleus (SPN) are enhanced by a very low intracellular chloride concentration, generated by the neuronal potassium chloride co-transporter (KCC2) expressed in the postsynaptic neurons. Our data show that modulation by NO caused a 15mV depolarizing shift of the IPSC reversal potential, reducing the strength of inhibition in SPN neurons, without changing the threshold for action potential firing. Regulating inhibitory strength, through cGMP-dependent changes in the efficacy of KCC2 in the target neuron provides a postsynaptic mechanism for rapidly controlling the inhibitory drive, without altering the timing or pattern of the afferent spike train. Therefore, this NO-mediated suppression of KCC2 can modulate inhibition in one target nucleus (SPN), without influencing inhibitory strength of other target nuclei (MSO, LSO) even though they are each receiving collaterals from the same afferent nucleus (a projection from the medial nucleus of the trapezoid body, MNTB).